2022
DOI: 10.3389/fimmu.2022.1028228
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: The emerging role of metabolism and metabolic-related receptors on neutrophil extracellular traps (NET) formation

Abstract: Editorial on the Research TopicThe emerging role of metabolism and metabolic-related receptors on neutrophil extracellular traps formation Neutrophils play a central role in host innate immunity as first cell line to fight pathogens; however, they are also being responsible for "collateral damage". Neutrophils have a wide repertoire of biological responses, including reactive oxygen species (ROS)dependent and -independent effector mechanisms. Release of neutrophil extracellular traps (NET) has been added as ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Nonetheless, different metabolic routes, including glycolysis with ATP generation, are required to fulfil energetic, biosynthesis, and defence functions of mammalian PMN [ 60 62 ]. Recently, it has been demonstrated that mammalian PMN can additionally rely on TCA cycle, oxidative phosphorylation (OXPHOS), pentose phosphate pathway (PPP), and fatty acid oxidation (FAO) for energy [ 63 , 64 ]. Overall, here we present new insights into early host innate immune response in vivo and in vitro of ovine PMN driven by F. hepatica considering ovine hosts as relevant and highly susceptible animals to fasciolosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, different metabolic routes, including glycolysis with ATP generation, are required to fulfil energetic, biosynthesis, and defence functions of mammalian PMN [ 60 62 ]. Recently, it has been demonstrated that mammalian PMN can additionally rely on TCA cycle, oxidative phosphorylation (OXPHOS), pentose phosphate pathway (PPP), and fatty acid oxidation (FAO) for energy [ 63 , 64 ]. Overall, here we present new insights into early host innate immune response in vivo and in vitro of ovine PMN driven by F. hepatica considering ovine hosts as relevant and highly susceptible animals to fasciolosis.…”
Section: Discussionmentioning
confidence: 99%